Willingness-to-pay in physical activity: how much older adults value the community-wide initiatives programs? - Somta, Sittichat; Völker, Marc; Widyastari, Dyah Anantalia; Mysook, Sirinapa; Wongsingha, Narakorn; Potharin, Danusorn; Katewongsa, Piyawat (Frontiers in Public Health, 2023)
Background Previous studies have shown insufficient physical activity (PA) as a significant global health concern and a major risk factor for non-communicable diseases (NCDs). Community-wide initiatives in physical activity (CWIPA) is considered as a best-buy for Community-wide initiatives in physical activity (CWIPA) is considered as a best-buy for NCDs prevention. However, assessment regarding resource allocation and cost-effectiveness of existing programs is lacking. This study investigated local residents’ willingness-to-pay (WTP) for community PA programs in Southern Thailand. Methods The contingent valuation method (CVM) using the payment card approach was employed to elicit the WTP of 472 residents aged 45 years and over in selected provinces in which community PA programs had been implemented. Respondents were asked to indicate their WTP for the continuous offering of free CWIPA by choosing how much they were willing to pay from eight bid-value options, payable through their monthly electricity bill. Results The mean WTP of Thai older adults was found to be 72 baht/month ($2/month) or 868 baht/year ($25/year). This indicated the maximum amount an older person was willing to pay for any community-based PA program. More than half the sample (54.2%) chose zero as their answer, while there was a fairly large variation in other levels of WTP. The WTP was lower among older respondents and those who resided in rural areas but was higher among those with a history of participation in an organized PA program. Conclusion The level of WTP can be interpreted as an indicator of community satisfaction with CWIPA. That finding can be used as evidence for the government and policy makers in allocating resources and designing future CWIPA. A variety of organized PA programs should be offered to all community members to ensure inclusivity and also to provide equal access for senior citizens.